ACUTE TONSILLITIS ON THE PEDIATRIC DISTRICT: ETIOLOGIC DIAGNOSIS AND TREATMENT - E. N. Cherkasova; T. A. Kuznetsova (Union of pediatricians of Russia, 2015)
Relevance. Acute tonsillitis is one of the most prevalent infectious diseases in children starting from the 6th month of live. Acute tonsillitis is more often triggered by viri rather than bacteria. Among the latter, the most significant etiological agent is the ß-hemolytic streptococcus of group A (BHSA). The difficulty of bacterial confirmation of a BHSA infection out-patient conditions, the fear of complications produce an excess usage of antibiotics while treating acute tonsillitis. It is possible to avoid the drawbacks of cultural studies (connected with a late response - around 4-5 days - and with the logistics of the material to the bacteriological laboratory) by using the highly specific and sensitive express-test, which allows to determine a BHSA etiology of the acute tonsillitis right at the patient's bed in 5-10 minutes. Aim: to optimize the diagnostics and treatment of acute tonsillitis in children in out-patient conditions. Patients and methods. In the conditions of a single paediatric district with 935 children aged 0 to 18 years 79 cases of acute tonsillitis were registered over the period of 1 year of surveillance. The criteria were: hyperemia of the back side of the throat, inflammation of the tonsils in the form of hyperemia/impositions. Along with general clinical methods all children received and additional express-test. Results. The population prevalence of acute tonsillitis was 84 per 1000 children, while the prevalence of BHSA-induced tonsillitis was 7.3 per 1000. The overall percentage of BHSA tonsillitis among other types of tonsillitis was 8.8%. Children with an acute BHSA-induced tonsillitis were prescrived with amoxicilline 50 mg/kg for 10 days. Conclusion. Using the express-diagnostics of the BHSA infection allows for a reduction in antibiotics usage in children with acute tonsillitis to 8.8%.